Az M6-os autópálya regionális hatásának bemutatása a Dél-Dunántúl régióban - Kovács, Áron (Jelenkori Társadalmi és Gazdasági Folyamatok, 2012)
The paper presents a research conducted on the M6 motorway in the Southern Transdanubian region. The basis of the research is data of 2006-2010 provided by the Hungarian Central Statistical Office. In the analysis I compare these measures only to themselves, assuming that they are independent from the sizes and economic potential of other regions. According to the findings of the research, it can be stated, that small regions closer to the highway benefit more from their state then those which are remote from it. Despite this small regional differences cannot be clearly linked only to the M6 highway, economic differences also prevail. In order to extend regional effects of the highway combined transportation developments would be necessary (water, rail, flight), and also the connection to with other highways in the Balkan region.